Bilateral Kinship and Inheritance Distribution in Dayak Indramayu Customary Law - Fansuri, Hamzah; Setyawan, Edy; Busthomi, Achmad Otong; Ali, Nur; Al Mustaqim, Dede; Dahlan, Rahman (Faculty of Law, Universitas Pattimura, 2025)
Introduction: The kinship system in the Dayak Indramayu community plays an important role in determining the pattern of inheritance distribution. Unlike the patrilineal or matrilineal systems, which emphasize a single line of descent, the Dayak Indramayu community adheres to a bilateral kinship system that allows inheritance rights to be obtained from both the father and mother.Purposes of the Research: This study aims to analyze how the bilateral kinship system influences the pattern of inheritance distribution in the Dayak Indramayu community, emphasizing aspects of gender equality, recognition of adopted children, and its implications for social justice within the framework of customary law and national law.Methods of the Research: This study uses a qualitative-descriptive method with a socio-cultural legal approach. Data was collected through field observations, semi-structured interviews with traditional leaders and community members, and documentation studies. Data analysis was conducted using Miles and Huberman's interactive model, supplemented with normative-legal interpretations to understand the relationship between traditional norms, social values, and positive law.Results of the Research: The study found that the bilateral kinship system of the Dayak Indramayu produces a relatively egalitarian inheritance pattern by granting equal rights to both sons and daughters. However, there are still weaknesses in guaranteeing the rights of adopted children and the potential for conflict due to differences in interpretation between subgroups. The originality of this research lies in its recommendation to reformulate customary law to be more adaptive to contemporary principles of social justice and in line with the national legal framework.